Mapping cancer research across Central and Eastern Europe, the Russian Federation and Central Asia: Implications for future national cancer control planning. (November 2018) - Begum, Mursheda; Lewison, Grant; Jassem, Jacek; Mixich, Vlad; Cufer, Tanja; Nurgozhin, Talgat; Shabalkin, Pavel; Kutluk, Tezer; Voko, Zoltan; Radosavljevic, Davorin; Vrdoljiak, Eduard; Eniu, Alexandru; et al.
Abstract: Cancer research is an essential part of national cancer control programmes, and the emerging economies of Central and Eastern Europe (CEE) and the Russian Federation and Central Asia (R-CA) (Commonwealth of Independent States) remain relatively understudied. Here, we map the cancer research activity from the 29 countries across these regions over a 10-year period (2007–2016), using a standard scientometric approach. Research activity was compared with the countries' wealth and with the disease burden from different cancers, and analyses were also performed by the research domain (e.g. fundamental cancer biology, surgery). We found that although there was a correlation between outputs and national wealth, there were many outliers; the CEE countries publishing relatively more, and the R-CA, less. Outputs reflected cancer burdens, but there was a relative paucity of research on lung, colorectal, gastric and pancreatic cancer, as well as research domains such as screening and palliative care. Clinical trials accounted for only 3% of all research outputs from all countries, and were very international, with on average 1.5 CEE countries and 8.0 others involved in each article, and they were heavily cited (on average, 84 times in 5 years). Poland was by far the most research-active country, but significant needs and opportunities have been identified to expand the cancer research activity in all CEE and R-CA countries to enhance national cancer control planning. Highlights: More cancer research is needed to improve cancer treatment in all countries. More research is needed on lung, colorectal, gastric and pancreatic cancers. There is a lack of research on screening and palliative care. European countries published more articles relative to their gross domestic product than Russia and Asia. Clinical trials totalled 3% of all articles that were very international and well cited.